A method for preparing double-layer WS2 nanomaterials with the assistance of carbon powder
By using toner reducing agent to convert WO3 in chemical vapor deposition method, the problem of thickness and crystal structure control of double-layer WS2 material is solved, the preparation and electrical performance of high-quality double-layer WS2 materials is achieved, and the cost of existing technology is solved The problem of meter-level pinning and low yield.
Patent Information
- Application Number
- CN202410013632.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-04
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-01-04
AI Technical Summary
The existing technology is difficult to effectively control the thickness and crystal structure of the two-layer two-dimensional transition metal chalcogenide (TMDs) nanomaterials, resulting in the problem of Fermi level pinning and low yield in device preparation, which limits its Applications in the field of optoelectronics.
By adding carbon powder as a reducing agent in the chemical vapor deposition method, the growth temperature and time are controlled, and the W6+ in WO3 is converted to W4+, thereby achieving the precise preparation of the double-layer WS2 material, promoting the vulcanization conversion process and improving the verticality of the material Growth.
The yield and electrical properties of the double-layer WS2 material have been successfully improved, good contact with metal electrodes has been achieved, the electrical properties of the device have been improved, and the possibility of large-area controllable installation on SiO2/Si substrates is provided.
Smart Images

Figure CN117766406B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of preparation of two-dimensional layered nanomaterials, and specifically relates to a method for preparing a double-layer tungsten disulfide nanomaterial with the aid of carbon powder. Background Art
[0002] Two-dimensional layered semiconductor materials, especially transition metal dichalcogenides (TMDs), have attracted widespread attention due to their excellent optoelectronic properties such as ultrathin structure, monolayer direct band gap, large exciton binding energy, room-temperature light emission, and potential applications in future integrated optoelectronic devices.
[0003] The layers of two-dimensional TMDs nanomaterials are usually bonded by strong covalent or ionic bonds, while the layers are stacked together by weaker van der Waals forces, and the layers can be easily separated by mechanical peeling. The physical and chemical properties of two-dimensional TMDs nanomaterials are related to their number of layers, which allows researchers to well control their optoelectronic properties by adjusting the thickness of the material. For example, as the number of layers of two-dimensional TMDs nanomaterials decreases, their band structure gradually changes from an indirect band gap to a direct band gap, accompanied by a widening of the band gap, making the material widely used in the field of optoelectronics. However, in the preparation of devices for single-layer TMDs nanomaterials, the deposited metal can easily damage the material, resulting in the Fermi level pinning phenomenon, which limits its application in the optoelectronic field.
[0004] Double-layer two-dimensional TMDs nanomaterials have high state density, higher mobility and driving current than their single layers, and have greater application prospects in field effect transistors, logic devices and sensors. At present, mechanical exfoliation is a simple method to obtain high-quality single-layer or multi-layer TMDs nanosheets, but its thickness and chip size are uncontrollable, and the yield is low, which hinders the further application of this method. Compared with the mechanical exfoliation method, chemical vapor deposition (CVD) is considered to be the preferred method for large-scale preparation of TMDs. For example, by controlling the magnetron sputtering of Mo film and WO 3 The film thickness can be 2 Atomic-scale MoS / Si substrate 2 and WS 2 Large-scale and tunable thickness growth of thin films. However, the multilayer MoS 2 and WS 2 The thin films are all polycrystalline. 2 Preparation of polycrystalline MoS with different number of layers on Si substrate 2 Although this method can obtain MoS with adjustable thickness 2Nanosheets, however, are difficult to control and the process is complex, which is not conducive to expanding production. Subsequently, researchers reported that a double-layer MoS with uniform thickness can be prepared along the edge of a C-plane sapphire surface with an engineered atomic platform height of 1.48 nm. 2 However, this technology is more suitable for sapphire substrates with orderly crystal structure and orientation, and for amorphous SiO2 that is compatible with device manufacturing processes. 2 However, it is impossible to controllably prepare double-layer two-dimensional TMDs nanomaterials on Si substrates. In contrast, bottom-up layer-by-layer growth may be a more feasible means of thickness control. However, due to the overhanging bondless surface and limited surface catalysts, the challenge is that the nucleation and growth of the upper layer on the lower layer are extremely difficult. Therefore, the controllable preparation of double-layer two-dimensional TMDs nanomaterials by CVD is still a huge problem that needs to be solved urgently. Summary of the invention
[0005] The present invention discloses a method for preparing a double-layer tungsten disulfide nanomaterial with the aid of carbon powder. By adding carbon powder to the raw material and controlling the growth temperature and growth time, W 6+ Transformed to W 4+ , to achieve precise control of double-layer WS 2 The purpose of the material preparation process is to prepare a double-layer WS with excellent electrical properties. 2 The device provides new ideas.
[0006] 1. Preparation of double-layer tungsten disulfide nanomaterials
[0007] 1) Put sulfur powder, and a mixture of tungsten trioxide, sodium chloride and carbon powder into the first quartz boat and the second quartz boat in the tube furnace respectively;
[0008] The first quartz boat is arranged close to the air inlet end of the tube furnace;
[0009] The second quartz boat is located in the middle of the tube furnace, and there is an inverted SiO 2 / Si substrate, inverted SiO 2 / The distance between the Si substrate and the mixture is 1~2mm;
[0010] The purity of sulfur powder, tungsten trioxide, sodium chloride and carbon powder is greater than 99.99%, and the mass ratio of sulfur powder to tungsten trioxide is 10:1, and the mass ratio of sodium chloride, tungsten trioxide and carbon powder is 1:35:3.5.
[0011] 2) Continuously introduce argon gas into the tubular furnace to exclude air; the flow rate of the introduced argon gas is 300~500sccm, and the introduction time is 15~20min.
[0012] 3) After the air in the tube furnace is completely removed, argon gas is continuously introduced and the temperature is raised to 950-1000°C for chemical vapor deposition reaction for 2-5 minutes; the tube furnace is then naturally cooled to room temperature to obtain a double-layer WS 2 Nanomaterials SiO 2 / Si substrate; during the chemical vapor deposition reaction, argon is used as the carrier gas, and the flow rate of the carrier gas is 90~110sccm.
[0013] The synthesis mechanism of the present invention:
[0014] As a reducing agent, carbon powder plays a vital role in the entire chemical vapor synthesis. Before the entire system reaches the reaction temperature, carbon powder and WO 3 Powder reaction to generate WO with lower W valence 3-x intermediate, x ranges from 0 to 1. We experimentally studied the evolution of the precursor during heating and confirmed that C 3 There is a W in 6+ The valence state plays a reducing role, converting it into WO with a lower valence state. 3-x ,like Figure 2 As shown in a.
[0015] In order to further study the effect of carbon on WO at high temperature 3 Reduction of the precursors: The carbon-containing and carbon-free precursor mixtures were heated at 950 °C. Figure 2 b is the Raman spectrum of the product. Original WO 3 At 714.7 and 806.8 cm -1 There are two Raman peaks at , which are the longer and shorter WOW bond stretching modes. 6+ The chemical bond ratio of the reduced tungsten ion (ie, W 5+ and W 4+ ) has a stronger chemical bond, W 6+ The Raman peak of the W bond appears at a higher energy, while 5+ and W 4+ The bond energy is low; for the precursor without C, at 712.5 cm -1 In contrast, in the presence of C precursor, the Raman peak shifts significantly to a lower wavelength of 676.4 cm -1 The significant shift of this Raman peak indicates that C 3 It has a strong reducing effect. It can be seen that carbon plays a vital role in the reduction process. During the heating process, carbon effectively converts WO 3 Reduced to WO with lower valence 3-x When the reaction reaches the preset temperature, WO 3 To WS 2The transformation process is performed by W 6+ To W 4+ A gradual transition process. In this process, WO 3-x S x Intermediates and WS x Clusters are formed in gaseous precursors, WO 3 The high WO bond energy and WO 3 Monoclinic unit cell and WS 2 In the hexagonal unit cell, the difference in the position of W atoms hinders the direct sulfurization of S powder, while the introduction of C powder helps to convert W into 6+ It is shown in previous literature that pure WO 3 The sulfurization formation energy of WO is 3.44 eV, while WO with oxygen vacancies 3-x The sulfurization formation energy of WO is significantly reduced to 2.55 eV. This difference in formation energy indicates that WO containing oxygen vacancies 3-x The sulfurization ratio of pure WO 3 Therefore, we introduced C powder to increase the high-density WO that is easy to vulcanize in the reaction. 3-x The possibility of intermediate generation makes it easier to control the bilayer WS in experiments 2 In addition, the oxidation of carbide byproducts such as CO and CO 2 More likely to be adsorbed during the growth process WS 2 The surface of the sheet provides heterogeneous nucleation sites, making the bilayer WS 2 Grow vertically rather than horizontally.
[0016] 2. Structural characterization of double-layer tungsten disulfide nanomaterials
[0017] The samples prepared in the embodiments of the present invention were subjected to structural characterization, and the results are as follows.
[0018] The double-layer WS prepared in the embodiment of the present invention was observed by optical microscope. 2 The surface morphology of the nanomaterials was characterized, and the single-layer and double-layer WS with and without carbon in the precursor were counted. 2 The average percentage (50 samples per group) is shown in the following table. Figure 3 As shown in the statistical chart, if the precursor does not contain carbon powder, the prepared WS 2 The monolayer rate of the sample reached 93%, and after adding carbon powder to the precursor, the prepared WS 2 The double layer rate of the sample reached 95%, which shows that carbon is 2 plays a vital role in the growth of.
[0019] Figure 4 The double-layer WS prepared in Example 1 of the present invention 2Optical photograph, where the growth time is 2 minutes; Figure 5 The double-layer WS prepared in Example 2 of the present invention 2 Optical photograph, where the growth time is 3 minutes; Figure 6 The double-layer WS prepared in Example 3 of the present invention 2 Optical photo, where the growth time is 5 minutes. Figures 4 to 6 As shown, as the growth time goes by, it can be observed that the top WS 2 The nanosheets grow layer by layer. Clear optical contrast photos show that the bilayer WS 2 The morphological transformation of the particles changes from incomplete stacking to complete stacking with the help of carbon as the growth time increases from 2 to 5 min. The corresponding local atomic force microscopy (AFM) images ( Figure 7 a-7c) clearly shows the prepared WS 2 It is a crystal with a clean, uniform surface and no impurities. Figure 7 The height analysis results in the inset of a-7c show that the SiO 2 / Si substrate surface to bottom WS 2 Nanosheets and then to the upper WS 2 The continuous height steps of the nanosheets confirm the layer-by-layer growth characteristics. 2 The thickness of the nanosheet is about 0.8 nm. 2 Nanosheets and SiO 2 There is a van der Waals gap between the / Si substrate, which makes the bottom WS 2 The thickness of the nanosheet is greater than that of the upper WS 2 The thickness of the nanosheet is nearly 1 nm, indicating that WS 2 Nanosheets on SiO 2 / The Si substrate surface grows layer by layer.
[0020] Raman spectroscopy has long been widely used in the study of the structure, film thickness and uniformity, internal and external strain of two-dimensional materials. 2 The nanosheets were characterized and the results are shown in Figure 8 As shown. Figure 8 a and 8b are SiO excited by 532 nm laser. 2 Single and double layers of WS on Si 2 Raman spectra of samples. 2 As an example, the Raman spectrum of the first-order optical mode E1 2g (in-plane vibration mode) and A 1g The frequency difference of the vibration mode (out-of-plane vibration mode) is 62 cm -1 In addition, A 1gThe blue shift of the mode becomes more obvious as the thickness of the layers increases. This is because as the number of layers increases, the WS 2 The interlayer coupling effect in the MoS 2 On the contrary, when the E1 2g mode increases from a single layer to a double layer, it undergoes a slight red shift, indicating that the effect of the increase in interlayer van der Waals forces is small, and the structural changes caused by stacking or the double-layer WS 2 The long-range Coulomb interlayer interaction in the double-layer WS 2 In the Raman spectrum of -1 and 416.8 cm -1 E1 2g and A were observed at 1g Raman peak, vibration mode frequency difference is 63.5 cm -1 When the thickness is reduced to a single layer, the Raman peak shifts to 355.4 cm -1 and 417.4 cm -1 This is completely consistent with the previous analysis and the previous report, which also proves that we have successfully prepared a high-quality double-layer WS 2 Single crystal film.
[0021] Photoluminescence spectroscopy (PL spectroscopy) is a direct method to detect the band gap of two-dimensional TMDs nanomaterials. 2 For the bulk material, it has an indirect band gap, and the PL emission peak is almost unobservable; while the single-layer material has a direct band gap, and a relatively obvious PL characteristic peak can be directly observed in the PL spectrum. Fig. 9 Shows a single layer WS 2 The characteristic peak of the PL characteristics of the crystal can be seen from the figure. At 1.967 eV (corresponding to a wavelength of about 630.4 nm), there is a very strong peak with a narrow half-peak width, indicating that the single-layer WS 2 The nanosheets have good quality; Fig.10 Shows a double layer WS 2 The characteristic peak of the PL characteristics of the crystal can be seen from the figure. There is also a peak at 1.917 eV (corresponding to a wavelength of about 647.37 nm), but this peak is not only weaker in intensity, but also wider in half-peak width, indicating that the material has a direct band gap transition to an indirect band gap. 2 PL peaks of nanosheets and bilayer WS 2 The PL peaks of the nanosheets are placed on the same coordinates. Fig.11 Shows a single layer WS 2 The PL peak of the nanosheets is similar to that of the bilayer WS 2 The results of comparing the PL peak intensity of the nanosheet by ten times show that the double-layer WS 2The PL peak intensity of the nanosheet is much weaker than that of the single-layer WS 2 The PL peak intensity of the nanosheets is attributed to the transition from direct bandgap (single layer) to indirect bandgap (double layer). 2 The position of the PL emission peak of the nanosheets is also consistent with previous reports.
[0022] 3. Performance evaluation of double-layer tungsten disulfide nanomaterials
[0023] In order to study the prepared single and double-layer WS 2 The electron transport performance of the triangular sheet was investigated by 2 Single-layer and double-layer WS 2 A typical optical photo of a triangular back-gate field effect transistor is shown in the figure below. Fig.12 a and Fig.13 As shown in a, it was electrically tested.
[0024] Fig.12 b and 12c are single-layer WS tested in atmospheric environment 2 The transfer characteristic curve of the device, Fig.12 d is a single-layer WS 2 Device output characteristic curve. From the transfer characteristic curve, we can calculate the single-layer WS 2 Mobility of triangular back-gate field-effect transistor: μ = 2.2 cm 2 V -1 s -1 , current switching ratio: I on / I of ≈10 5 ; From the output characteristic curve, we can see that the source-drain current-source-drain voltage ( I ds − V ds ) is a nearly linear relationship, indicating that the single-layer WS 2 There is a certain potential barrier between the material and the metal electrode.
[0025] Fig.13 b and 13c are double-layer WS tested in atmospheric environment 2 The transfer characteristic curve of the device, Fig.13 d is double-layer WS 2 Output characteristic curve of the triangular device. From the transfer characteristic curve, we can calculate the double-layer WS 2 Mobility of triangular back-gate field-effect transistor: μ = 19.5 cm 2 V -1 s -1 , current switching ratio: I on / I of ≈107 ; From the output characteristic curve, it can be seen that the source I ds − V ds There is a very good linear relationship, indicating that the double-layer WS 2 An ohmic contact is formed between the material and the metal electrode, resulting in better electrical performance.
[0026] In summary, the preparation method of the present invention is simple and has good experimental repeatability. Adding carbon powder can effectively prepare high-quality double-layer WS 2 The electrical properties of the double-layer WS 2 The material has good contact with the metal electrode and improves its electrical properties. At the same time, the preparation method of the present invention can be extended to other double-layer two-dimensional TMDs nanomaterials. The prepared two-dimensional TMDs nanomaterials have extremely high quality and are of great significance for the study of nanoscale light-emitting devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The double-layer WS of the present invention 2 Schematic diagram of the preparation process of nanomaterials;
[0028] Figure 2 The double-layer WS of the present invention 2 During the preparation of nanomaterials, C reacts with WO 3 Raman diagram of reduction. Figure 2 a is WO collected at different temperatures 3 +C precursor Raman spectrum, Figure 2 b is the original WO collected at 950℃ 3 , WO 3 +NaCl mixture, WO 3 +NaCl+C mixture Raman spectrum;
[0029] Figure 3 WS prepared without adding carbon powder and with adding carbon powder in Example 1 of the present invention 2 Statistical graphs of single and double layer rates of nanomaterials;
[0030] Figure 4 The double-layer WS prepared in Example 1 of the present invention 2 Optical photographs of nanomaterials;
[0031] Figure 5 The double-layer WS prepared in Example 2 of the present invention 2 Optical photographs of nanomaterials;
[0032] Figure 6 The double-layer WS prepared in Example 3 of the present invention 2 Optical photographs of nanomaterials;
[0033] Figure 7 The double-layer WS prepared in Examples 1 to 3 of the present invention 2 Atomic force microscopy (AFM) images of nanomaterials, including: Figure 7 a is the double-layer WS prepared in Example 1 of the present invention 2 AFM photos of nanomaterials. Figure 7 b is the double-layer WS prepared in Example 2 of the present invention 2 AFM photos of nanomaterials. Figure 7 c is the double-layer WS prepared in Example 3 of the present invention 2 AFM photos of nanomaterials;
[0034] Figure 8 SiO2 excited by 532 nm laser 2 Single and double layers of WS on / Si 2 Raman spectrum of the sample, where: Figure 8 a is a single-layer WS prepared in Example 2 of the present invention 2 Raman images of nanomaterials. Figure 8 b is the double-layer WS prepared in Example 2 of the present invention 2 Raman images of nanomaterials;
[0035] Fig. 9 The single-layer WS prepared in Example 2 of the present invention 2 PL spectra of nanomaterials, where: Fig. 9 a is the relationship between wavelength and peak intensity, Fig. 9 b is the relationship between photon energy and peak intensity;
[0036] Fig.10 The double-layer WS prepared in Example 2 of the present invention 2 PL spectra of nanomaterials, where Fig.10 a is the relationship between wavelength and peak intensity, Fig.10 b is the relationship between photon energy and peak intensity;
[0037] Fig.11 The double-layer WS prepared in Example 2 of the present invention 2 Nanomaterials and monolayer WS 2 Comparison of PL spectra of nanomaterials;
[0038] Fig.12 a is a single layer WS prepared in Example 1 of the present invention without adding carbon powder 2 A typical optical photograph of a device fabricated using electron beam etching. Fig.12 b and Fig.12 c is a single-layer WS 2 The transfer characteristic curve of the triangle device, Fig.12d is a single-layer WS 2 Output characteristic curve of triangle device;
[0039] Fig.13 a is the double-layer WS prepared in Example 3 of the present invention 2 A typical optical photograph of a device fabricated using electron beam etching. Fig.13 b and Fig.13 c is a double-layer WS 2 The transfer characteristic curve of the triangular device, Fig.13 d is double-layer WS 2 Output characteristic curve of the triangle device. DETAILED DESCRIPTION
[0040] The present invention is further explained below with reference to specific embodiments.
[0041] The equipment used in the following examples is: a horizontal tube furnace with a tube length of 100 cm, a heating zone length of about 55 cm, a maximum temperature setting of 1200° C., a heating rate of 30° C. / min, and a quartz tube diameter of 2 inches.
[0042] Example 1
[0043] 1) First, buy 300nm SiO 2 / Si wafer cut into 1.5cm * 1.5 cm substrate for standby use; secondly, use detergent, deionized water, ethanol and acetone solution to clean the cut 300 nm SiO 2 / Si silicon wafer substrate is ultrasonically cleaned and then blown dry with a nitrogen gun for later use;
[0044] 2) Weigh 35 mg of WO 3 Powder, 1 mg of NaCl powder, 3.5 mg of C powder were evenly mixed, ground in a mortar for 2 minutes, and then the evenly mixed powder was placed in a ceramic boat; 350 mg of S powder was weighed and placed in another ceramic boat;
[0045] At the same time, take the same weight of WO 3 powder, NaCl powder and S powder were placed in two new ceramic boats for carbon-free powder preparation;
[0046] 3) The cleaned 300nm SiO 2 / Si silicon wafer substrate is flatly buckled on the WO 3 Mix the powders on a ceramic boat and place an inverted SiO 2 The distance between the Si substrate and the mixture is about 1.5 mm, and the ceramic boat is placed in the central temperature zone of the tube furnace, and the ceramic boat containing S powder is placed in the upstream of the tube furnace (such as Figure 1As shown). At room temperature, 500 sccm of argon (purity of 99.999%) was introduced into the tube furnace for about 20 minutes to eliminate the influence of the remaining air in the tube furnace on the sample growth;
[0047] 4) Then, the tube furnace is quickly heated to 150°C, the flow rate of the carrier gas argon is adjusted to 100 sccm, and the temperature is kept for 5 minutes to remove water vapor, etc.; then the temperature is continued to be raised. When the temperature in the tube furnace reaches 950°C, the reaction time is about 2 minutes; after the reaction is completed, the heating is stopped and the tube furnace automatically cools to room temperature.
[0048] Example 2
[0049] 1) First, buy 300nm SiO 2 / Si wafer cut into 1.5cm * 1.5 cm substrate for standby use; secondly, use detergent, deionized water, ethanol and acetone solution to clean the cut 300 nm SiO 2 / Si silicon wafer substrate is ultrasonically cleaned and then blown dry with a nitrogen gun for later use;
[0050] 2) Weigh 35 mg of WO 3 Powder, 1 mg of NaCl powder, 3.5 mg of C powder were evenly mixed, ground in a mortar for 2 minutes, and then the evenly mixed powder was placed in a ceramic boat; about 350 mg of S powder was weighed and placed in another ceramic boat;
[0051] At the same time, take the same weight of WO 3 powder, NaCl powder and S powder were placed in two new ceramic boats for carbon-free powder preparation;
[0052] 3) The cleaned 300nm SiO 2 / Si silicon wafer substrate is flatly buckled on the WO 3 Mix the powders on a ceramic boat and place an inverted SiO 2 The distance between the Si substrate and the mixture is about 1.5 mm, and the ceramic boat is placed in the central temperature zone of the tube furnace, and the ceramic boat containing S powder is placed in the upstream of the tube furnace (such as Figure 1 As shown). At room temperature, 500 sccm of argon (purity of 99.999%) was introduced into the tube furnace for about 20 minutes to eliminate the influence of the remaining air in the tube furnace on the sample growth;
[0053] 4) Then, the tube furnace is quickly heated to 150°C, the flow rate of the carrier gas argon is adjusted to 100 sccm, and the temperature is kept for 5 minutes to remove water vapor, etc.; then the temperature is continued to be raised. When the temperature in the tube furnace reaches 950°C, the reaction time is about 3 minutes; after the reaction is completed, the heating is stopped and the tube furnace automatically cools to room temperature.
[0054] Example 3
[0055] 1) First, buy 300nm SiO 2 / Si silicon wafers were cut into 1.5cm*1.5cm substrates for standby use; secondly, detergent, deionized water, ethanol and acetone solutions were used to clean the cut 300nm SiO 2 / Si silicon wafer substrate is ultrasonically cleaned and then blown dry with a nitrogen gun for later use;
[0056] 2) Weigh 35 mg of WO 3 Powder, 1 mg of NaCl powder, 3.5 mg of C powder were evenly mixed, ground in a mortar for 2 minutes, and then the evenly mixed powder was placed in a ceramic boat; about 350 mg of S powder was weighed and placed in another ceramic boat;
[0057] 3) The cleaned 300nm SiO 2 / Si silicon wafer substrate is flatly buckled on the WO 3 Mix the powders on a ceramic boat and place an inverted SiO 2 The distance between the Si substrate and the mixture is about 1.5 mm, and the ceramic boat is placed in the central temperature zone of the tube furnace, and the ceramic boat containing S powder is placed in the upstream of the tube furnace (such as Figure 1 As shown). At room temperature, 500 sccm of argon (purity of 99.999%) was introduced into the tube furnace for about 20 minutes to eliminate the influence of the remaining air in the tube furnace on the sample growth;
[0058] 4) Then, the tube furnace is quickly heated to 150°C, the flow rate of the carrier gas argon is adjusted to 100 sccm, and the temperature is kept for 5 minutes to remove water vapor, etc.; then the temperature is continued to be raised. When the temperature in the tube furnace reaches 950°C, the reaction time is about 5 minutes; after the reaction is completed, the heating is stopped and the tube furnace automatically cools to room temperature.
Claims
1. A method for preparing double-layer WS2 nanomaterials with the aid of carbon powder, characterized in that: The following steps are involved: 1) Put sulfur powder into the first quartz boat in the tube furnace, and put a mixture of tungsten trioxide, sodium chloride and carbon powder into the second quartz boat in the tube furnace; the mass ratio of sulfur powder to tungsten trioxide is 10:1, and the mass ratio of sodium chloride, tungsten trioxide and carbon powder is 1:35:3.5; The first quartz boat is arranged close to the air inlet end of the tube furnace; The second quartz boat is located in the middle of the tube furnace, and a SiO2 / Si substrate is inverted on the second quartz boat, and the distance between the inverted SiO2 / Si substrate and the mixture is 1-2 mm; 2) Continuously introduce argon gas into the tube furnace to exclude air; 3) After the air in the tube furnace is completely removed, argon gas is continued to be introduced and the temperature is raised to 950~1000℃ for chemical vapor deposition reaction for 2~5min; then the tube furnace is naturally cooled to room temperature to obtain a SiO2 / Si substrate with a double-layer WS2 nanomaterial grown on it.
2. A method for preparing a double-layer WS2 nanomaterial with the aid of carbon powder as claimed in claim 1, characterized in that: In step 2), the flow rate of argon gas is 300-500 sccm, and the duration of the introduction is 15-20 min.
3. A method for preparing a double-layer WS2 nanomaterial with the aid of carbon powder as claimed in claim 1, characterized in that: In step 3), during the chemical vapor deposition reaction, argon is used as a carrier gas, and the flow rate of the carrier gas is 90-110 sccm.
4. A double-layer WS2 nanomaterial prepared by the method as claimed in claim 1.
5. A double-layer WS2 nanomaterial as claimed in claim 4, characterized in that: The area of the upper WS2 layer projected in the vertical direction is less than or equal to the area of the lower WS2 layer projected in the vertical direction, and the crystal coverage of the upper WS2 layer is 50%~100%.
6. Application of the double-layer WS2 nanomaterial prepared by the method as claimed in claim 1 in a back-gate field effect transistor.
Citation Information
Patent Citations
Supercapacitor electrode material tungsten sulfide-carbon aerogel and preparation method thereof
CN105719845A
Preparation method of manganese-doped single-layer tungsten disulfide two-dimensional crystal
CN111285401A
Preparation method of tungsten disulfide single crystal with controllable layer number
CN111472049A
Method for growing two tungsten disulfide thin layers under normal pressure
CN113930743A
Tungsten disulfide field effect transistor based on 3R phase and preparation method thereof
CN115483290A
